Silencing of miR490–3p by H. pylori activates DARPP-32 and induces resistance to gefitinib. (28th October 2020) - Zhu, Shoumin; Khalafi, Shayan; Chen, Zheng; Poveda, Julio; Peng, Dunfa; Lu, Heng; Soutto, Mohammed; Que, Jianwen; Garcia-Buitrago, Monica; Zaika, Alexander; El-Rifai, Wael
Abstract: Infection with Helicobacter pylori ( H. pylori ) is the main risk factor for gastric carcinogenesis. In this study, we investigated the expression, molecular functions, and downstream effectors of miR490–3p in gastric cancer. We used in vitro and in vivo models to investigate the role of H. pylori in regulating miR490–3p, DARPP-32-dependent functions, and therapeutic resistance. Human and mouse neoplastic gastric lesions demonstrated a negative correlation between DARPP-32 and miR490–3p expression (R = −0.58, P < 0.01). This was also detected following infection with H. pylori (R = −0.66, P < 0.01). Molecular assays confirmed DARPP-32 as a direct target of miR490–3p. CHRM2, the host gene of miR490–3p, was hypermethylated and downregulated in neoplastic gastric tissues ( P < 0.05). H. pylori induced methylation and downregulation of CHRM2 and miR490–3p. Functionally, the reconstitution of miR490–3p sensitized cancer cells to gefitinib by inactivating DRAPP-32-dependent AKT and STAT3 pathways. Patients with low miR490–3p or high DARPP-32 expression had decreased overall survival ( P < 0.05). Hypermethylation-mediated silencing of CHRM2 and miR490–3p by H. pylori increased DARPP-32 expression. Downregulation of miR490–3p in gastric cancer plays a role in gefitinib response by inducing DARPP-32-mediated activation of PI3K/AKT, STAT3 signaling pathways. Highlights: Molecular mechanisms that contribute to frequent overexpression of DARPP-32 in gastric cancer remain largely unknown. Bioinformatics analysis identified downregulation of miR490-3p with predictive binding sites on DARPP-32 3'TR. Hypermethylation-mediated silencing of CHRM2 and miR490-3p by H. pylori were demonstrated. miR490-3p downregulation played a role in gefitinib response by inducing DARPP-32-mediated activation of AKT and STAT3.